Factors Affecting Adverse Events Following SARS-CoV-2 Vaccine among Indonesian Ear, Nose, and Throat Specialist, and Residences - Susyana Tamin; Jenny Bashiruddin; Indra Zachreini; Harim Priyono; Ika Dewi Mayangsari; Respati Ranakusuma; Natasha Supartono; Khoirul Anam; Anggina Diksita; Yussy Afriana Dewi; Sagung Rai Indrasari; Nyilo Purnami; Tengku Siti Hajar Haryuna; Juliandi Harahap; Eka Savitri; Tjandra Manukbua (eJournal Kedokteran Indonesia, 2022)
This study’s objectives were to investigate factors affecting the adverse events of the COVID-19 vaccine in Indonesia among health care workers and compare adverse events following SARS-CoV-2 vaccine using CoronaVac as the first and second dose and Moderna used as the booster third dose. A cross-sectional study was conducted using the Self-reporting Online Survey Platform (Google Form) from August to October 2021. Subjects included in the study were ENT specialists and residents all over Indonesia who had been vaccinated with both doses of CoronaVac COVID-19 vaccine and Moderna COVID-19 vaccine as a booster dose. Among a total of 1394 participants, 51.2% and 43.7% of subjects experienced adverse events following the first and second dose of the CoronaVac vaccine. Adverse events are significantly higher following the third dose of Moderna vaccine (95.3%) with p-value <0.001, odds ratio (OR) 26.63 (95% CI 19.87-35.7). Adverse events following the CoronaVac vaccine were significantly higher in females and individuals with comorbidities in the first dose (p=0.002 and p=0.04), and the second dose (p=0.008 and p=0.042). Adverse events following the Moderna vaccine were significantly higher in females (p=0.01) and lower in individuals ≥40 years of age (p=0.017). Comorbidity status did not affect adverse events following the Moderna vaccine. Keywords: adverse events, SARS-CoV-2, COVID-19, vaccine, otorhinolaryngology.   Faktor yang Mempengaruhi Efek Samping Vaksin SARS-CoV-2 terhadap Dokter Spesialis dan Residen Telinga, Hidung, dan Tenggorok di Indonesia Abstrak Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi efek samping vaksin COVID-19 di Indonesia pada petugas kesehatan dan membandingkan efek samping setelah vaksin SARS-CoV-2 menggunakan CoronaVac sebagai dosis pertama dan kedua dan Moderna sebagai booster dosis ketiga. Studi potong lintang dilakukan dengan menggunakan self-reporting survei online (Google Form) dari Agustus-Oktober 2021. Subjek yang termasuk dalam penelitian adalah dokter residen dan spesialis THT di Indonesia yang telah divaksinasi dengan kedua dosis vaksin CoronaVac COVID-19 dan vaksin Moderna COVID-19 sebagai dosis tambahan. Dari total 1394 peserta, 51,2% dan 43,7% subjek mengalami efek samping setelah dosis pertama dan kedua vaksin CoronaVac. Efek samping secara signifikan lebih tinggi setelah dosis ketiga vaksin Moderna (95,3%) dengan p-value <0,001, rasio odds (OR) 26,63 (95% CI 19,87-35,7). Efek samping setelah vaksin CoronaVac secara signifikan lebih tinggi pada wanita dan individu dengan penyakit penyerta pada dosis pertama (p=0,002 dan p=0,04), dan dosis kedua (p=0,008 dan p=0,042). Efek samping setelah vaksin Moderna secara signifikan lebih tinggi pada wanita (p=0,01), dan lebih rendah pada individu ≥ 40 tahun (p=0,017). Status komorbiditas tidak mempengaruhi efek samping setelah vaksin Moderna. Kata kunci: efek samping, SARS-CoV-2, COVID-19, vaksin, otorinolaringologi.